APLIKASI COMPOS TEA TERINDUKSI INOKULUM FUNGI LIGNOSELULOLITIK PADA MEDIA TANAM COCOPEAT TERHADAP PERTUMBUHAN TANAMAN BAYAM MERAH (Amaranthus tricolor L.): APLIKASI COMPOS TEA TERINDUKSI INOKULUM FUNGI LIGNOSELULOLITIK PADA MEDIA TANAM COCOPEAT TERHADAP PERTUMBUHAN TANAMAN BAYAM MERAH (Amaranthus tricolor L.) - Ayu Wulan Septitasari Ayu; Bambang Irawan; Rochma Agustrina; Endang Nurcahyani; Sri Wahyuningsih (Politeknik Negeri Lampung., 2021)
Compost tea is a source of additional nutrients that are easily utilized by plants along with water absorption so that it can improve plant growth. Apart from nutrients, the planting medium also plays an important role in supporting plant growth. Cocopeat is a good growing media composition because it can bind water and soil nutrients by forming storage pores so that the nutrients in the soil do not dissolve easily. The purpose of this study was to determine the effect of giving Compost tea induced by lignocellulolytic fungal inoculum on cocopeat growing media on the growth of red spinach (Amaranthus tricolor L.) and the effect of the interaction between compost tea and the ratio of cocopeat: the best soil to increase spinach plant growth. red. This research was carried out from May to July 2020 at the greenhouse of the Integrated Field Laboratory of the Faculty of Agriculture, University of Lampung. This study used a Factorial Completely Randomized Design (CRD) with the first factor (A) is compost tea with 2 levels, namely compost tea aerated (ACT) A1 and compost tea non-aerated A2, and the second factor (B) is planting media using 3 levels, namely ( B1) cocopeat and soil (2: 1), (B2) cocopeat and soil (1: 1), (B3) cocopeat and soil (1: 2) with control was only used as a comparison of the average value. Each treatment unit was carried out. as much as 4 repetitions. The parameters observed included the number of leaves. Analysis of variance at the significance level of α 5%. Then to see the difference between treatments with Tukey's test at the significant level of α 5%. The results of this study indicate that ACT and cocopeat growing media: soil = 1: 2, as well as the interaction of the two produces the highest value compared to other treatments.